Sum rules for hadron photoproduction on hadrons and photon - Bartoš, E. (Array, 2008)
Summary: Sum rules are derived relating mean-squared charge radii in the case of pseudoscalar meson, Dirac mean-squared radii and anomalous magnetic moments in the case of (1/2)+ baryon, and finally sum of ratios of the fourth power of quark charges to the squared quark masses in the case of photon, with convergent integrals over the hadron photoproduction total cross-sections on pseudoscalar mesons, octet baryons and over gg® 2 jets cross-section, respectively. As a byproduct, chains of inequalities for corresponding total photoproduction cross-sections on meson and baryons in finite energy region, to be valid on an average, are also derived